2022
DOI: 10.1002/adsc.202200124
|View full text |Cite
|
Sign up to set email alerts
|

N‐Hydroxyphthalimide Catalyzed Aerobic Oxidation of Aldehydes under Continuous Flow Conditions

Abstract: The efficacy of synthetic methodologies is based not only on potent chemistries but also on processing strategies that amplify reaction performance and overall safety. The N-hydroxyphtalimide-catalyzed aerobic oxidation of aldehydes is an environmentally reliable and inexpensive approach for the synthesis of valuable carboxylic acids. However, the reaction may lead to the accumulation of significant amounts of peracid in crude product mixtures thereby generating a considerable safety hazard. Also, in the case … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 65 publications
0
12
0
Order By: Relevance
“…In addition, in recent literature, it is suggested that the formation of the Criegee intermediate V is a slow process and alternative pathways are proposed for the generation of acid under non-irradiating conditions, however, we could not detect such intermediates in our study. 10 b ,32,33 Thus, fast trapping of IV by acetone to VI could explain the faster formation of acid. Collectively, the study of the reaction mechanism by DI-HRMS suggests a solvent-accelerating process, which involves a dioxirane oxidant in situ generated under these reaction conditions, highlighting the importance of DI-HRMS as a tool to study organic chemistry reactions.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, in recent literature, it is suggested that the formation of the Criegee intermediate V is a slow process and alternative pathways are proposed for the generation of acid under non-irradiating conditions, however, we could not detect such intermediates in our study. 10 b ,32,33 Thus, fast trapping of IV by acetone to VI could explain the faster formation of acid. Collectively, the study of the reaction mechanism by DI-HRMS suggests a solvent-accelerating process, which involves a dioxirane oxidant in situ generated under these reaction conditions, highlighting the importance of DI-HRMS as a tool to study organic chemistry reactions.…”
Section: Resultsmentioning
confidence: 99%
“…We have shown that pathway B, via the Criegee intermediate, could be neglected for aliphatic and aromatic aldehydes. 8 In particular, we 8,9 and others 10,11 have shown that the peracid 4 accumulated in the reaction mixture. Peracid 4 is converted into carboxylic acid 6 during workup (Scheme 1, pathway C) or using a metal catalyst.…”
Section: Introductionmentioning
confidence: 65%
“…Nevertheless, the problem of selectivity for aliphatic aldehydes, particularly for β-substituted aliphatic aldehydes remains. 8,10,11,[13][14][15][16][17] A carboxylic acid selectivity between 70% and 90% without additives was observed for 2-ethylhexanal 1, an industrially important chemical intermediate. 18 It has already been shown that the selectivity towards 2-ethylhexanoic acid 6 was also dependent on the solvent.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations